Metal-free [3+3] benzannulation of 1-indanylidene-malononitrile with Morita–Baylis–Hillman carbonates: direct access to functionalized fluorene and fluorenone derivatives. Issue 13 (28th January 2020) - Xie, Ya-Sa; Huang, Run-Feng; Li, Ran; Zhang, Chuan-Bao; Fu, Ji-Ya; Zhao, Li-Li; Yuan, Jin-Fang
Abstract : An efficient [3+3] benzannulation of Morita–Baylis–Hillman carbonates with 1-indanylidenemalononitrile was achieved selectively delivering a wide range of functional fluorene or fluorenone compounds in high yields (up to 86% yields). Abstract : An efficient [3+3] benzannulation of Morita–Baylis–Hillman carbonates with 1-indanylidenemalononitrile was achieved under metal-free reaction conditions selectively delivering a wide range of functional multi-substituted fluorene or fluorenone compounds in high yields, respectively (up to 86% yield). Moreover, experiments and quantum chemical calculations were also performed to study the mechanism of the transformation.